Next-generation multitarget stool DNA vs fecal immunochemical test in colorectal cancer screening - Seum, Teresa; Niedermaier, Tobias; Heisser, Thomas; Hoffmeister, Michael; Brenner, Hermann (JAMA internal medicine, 2025)
Fecal immunochemical tests (FITs) are the most widely used noninvasive colorectal cancer (CRC) screening tests. In 2014, a US/Canadian screening study reported higher sensitivity of a multitarget stool DNA test (MSDT), which combined fecal hemoglobin measurement with molecular DNA markers, compared with a commercial FIT. However, this increase in sensitivity was accompanied by a substantial loss of specificity. Despite 20-fold higher per-sample costs, use of MSDT-based screening strongly increased in the US in recent years. Recently, Imperiale et al evaluated diagnostic performance of a next-generation MSDT (NG-MSDT) in another screening colonoscopy cohort (BLUE-C study). Sensitivity was higher than that of a commercial FIT, although again specificity was lower. It was previously shown that lowering the positivity threshold of a commercial quantitative FIT could enhance diagnostic performance to be comparable to a multitarget stool ribonucleic acid (RNA) test, prompting an evaluation of whether the same approach could yield similar outcomes with the NG-MSDT.
Online veröffentlicht: November 18, 2024
Gesehen am 27.06.2025